Combined sodium glucose co‐transporter‐2 inhibitor and angiotensin‐converting enzyme inhibition upregulates the renin‐angiotensin system in chronic kidney disease with type 2 diabetes: Results of a randomized, double‐blind, placebo‐controlled exploratory trial. Issue 5 (24th January 2022) - Antlanger, Marlies; Domenig, Oliver; Kaltenecker, Christopher C.; Kovarik, Johannes J.; Rathkolb, Vincent; Müller, Martin M.; Schwaiger, Elisabeth; Hecking, Manfred; Poglitsch, Marko; Säemann, Marcus D.; Kopecky, Chantal
Abstract: Aim: Sodium glucose co‐transporter‐2 inhibitors (SGLT‐2i) improve cardiorenal outcomes in patients with chronic kidney disease (CKD), with and without type 2 diabetes. The molecular mechanisms underlying these pleiotropic effects remain unclear, yet it is speculated that SGLT‐2i elicit a neurohormonal modulation resulting in renin‐angiotensin system (RAS) activation. We hypothesized that combined SGLT‐2 and angiotensin‐converting enzyme inhibition (ACEi) favours RAS regulation towards the beneficial angiotensin‐(1‐7)‐driven axis. Materials and Methods: This randomized controlled prospective study investigated the effect of 12 weeks treatment with the SGLT‐2i empagliflozin on top of ACEi on the molecular RAS dynamics in 24 diabetic and 24 non‐diabetic patients with CKD. Systemic RAS peptides were quantified by mass spectrometry. Results: In patients with type 2 diabetes, combined SGLT‐2i and ACEi significantly upregulated plasma renin activity [pre‐treatment median and interquartile range 298.0 (43.0‐672.0) pmol/L versus post‐treatment 577.0 (95.0‐1543.0) pmol/L; p = .037] and angiotensin I levels [pre‐treatment 289.0 (42.0‐668.0) pmol/L versus post‐treatment 573.0 (93.0‐1522.0) pmol/L; p = .037], together with a significant increase of angiotensin‐(1‐7) levels [pre‐treatment 14.0 (2.1‐19.0) pmol/L versus post‐treatment 32.0 (5.7‐99.0) pmol/L; p = .012]. Empagliflozin treatment resulted in a 1.5 to 2‐fold increase in main RAS peptides in patients with diabetes compared with placebo. No significant effect of empagliflozin on top of ACEi on RAS peptides was found in patients with CKD without diabetes. Conclusion: A distinct RAS modulation by SGLT‐2i occurs in diabetic kidney disease reflected by enhancement of the beneficial angiotensin‐(1‐7) providing a molecular background for this renoprotective therapeutic approach.